Carta de José Celso Barbosa a Roberto H. Todd - Barbosa, José Celso; Todd, Roberto H. (My University, 1908)
Nombramiento de Travieso y José Celso Barbosa.
Keywords: Puerto Rico--Politics and government.; Puerto Rico--Política y gobierno.